Drying kinetics of brick in a convective hot air dryer - Ahmet Cihan; Dinser Akal; Kamil Kahveci (Промышленная теплотехника, 2005)
In this study, drying characteristics of brick have been investigated experimentally. Evaluating experimental results under these circumstances diffusion coefficients and drying diagrams were determined.